THE REALITY OF LEARNING AND CAPACITY-BASED FULFILLMENT AT DARUL MA'ARIF ISLAMIC BOARDING SCHOOL IN JAYAPURA - Nawir, M. Syukri; Rama, Bahaking; Damopolii, Muljono; Munir, Munir (Jurnal Diskursus Islam, 2020)
This paper will elaborate deeply on the reality of learning and capacity-based fulfillment at Darul Ma'arif Islamic Boarding School in Jayapura City. Qualitative descriptive research type, conducted on primary and secondary data sources with a phenomenological approach from a methodological perspective, educational sociology and educational psychology from a scientific perspective using interview guidelines, observation sheets, and documentation tools as instruments to collect data that are processed and analyzed using reduction techniques. data, data presentation, and data conclusions, and validity is tested by triangulation techniques and observation extension. The results showed that learning is carried out classically using formal standard methods, in addition to takhassus learning that studies classical Islamic books that bring results to the ability to memorize the Koran, mastering Arabic and English, and mastery of reading books in limited quantities. The fulfillment of capacity at the Darul Ma'arif Islamic Boarding School in Jayapura City is illustrated, that the aspects of the kiai were not found in the three boarding schools, students from simple family backgrounds, education facilities and infrastructure built from natural materials with semi-permanent capacity. limited, and the same curriculum refers to the Ministry of Religion.